Osteogenic Potential Differentiation of Human Amnion Mesenchymal Stem Cell with Chitosan-Carbonate Apatite Scaffold (In Vitro Study) - Kamadjaja, Michael J.K.; Salim, Sherman; Rantam, Fedik A. (BALI MEDICAL JOURNAL; Vol 5 No 3 (2016), 2016)
Background: Tissue engineering based approaches have received much attention. Incorporation of chitosan and carbonate apatite (CA) improve its capability. Human mesenchymal stem cells (hMSCs) is viable for xenogenic transplantation. The purpose of this study was to fabricate and evaluate the osteogenic potential differentiation of human amnion mesenchymal stem cell with carbonate apatite– chitosan scaffolds (CA-ChSs) for tissue engineering. Method: Human amniotic membrane was procured from using cesarean section. Soncini’s protocol was employed for the isolation procedure. The cells cultured on collagen-coated dishes using Dulbecco's minimal essential medium (DMEM)/F12 (1:1). A chitosan powder of medium molecular weight deacetylated chitin, poly(D(glucosamine) was used and mixed with CA. Immunocytochemistry and flowcytometry used for phenotypic characterization of hAMSC. Result: Amniotic membrane obtained using cesarean section under aseptic condition did not exhibit any growth of cell cultures which were not contaminated. Immunocytochemistry testing revealed that the target cells expressed strong mesenchymal stem cell marker CD 105. Characterization at passage 10 showed that CD44 was the most significant and abundant surface receptors. The number of viable cells in chitosan-carbonate apatite was 66.59%. Scanning electron microscope (SEM) observation revealed that CA-ChSs had three-dimensional structure with many pores and hAMSc could attached and proliferation among the porosity of the scaffold. The formation of calcium in the cell as an indicator of osteoblast cells was detected using Alizarin Red solution. Conclusion: hAMSc harvested from human amniotic membrane seeding in CA- ChSs had the capability for in vitro osteogenesis makes them be the one of the potential options for bone tissue engineering.
Keywords: human amniotic membrane mesenchymal stem cells, chitosan-carbonate apatite, scaffold, MSC phenotypic characterization, MTT assay.